Regulation and Implementation of Green Open Space in Indonesia: Between Policy and Reality (Case Study at JIS Stadium) - Sada Arifin; Sadino Sadino; Anas Lutfi (Bina Nusantara University, 2025)
Green Open Space (RTH) has a vital function in maintaining ecosystem balance, improving air quality, and providing healthy and comfortable public spaces for the community. The role of green spaces is becoming increasingly important in the midst of increasing urbanization and rapid infrastructure development. In Indonesia, the government has established various regulations to ensure the availability of green spaces, including through Law No. 26/2007 on Spatial Planning which requires a minimum of 30% of the total city area to be allocated for green spaces. However, implementation in various regions, including in strategic areas such as the Jakarta International Stadium (JIS), still faces serious challenges. This study uses a juridical normative method to analyze the policy and implementation of the RTH regulation and assess the extent to which the JIS area complies with the regulation. The findings show that despite the existence of a strong legal foundation, the implementation of the RTH policy is still constrained by land conversion for commercial purposes, weak inter-agency coordination, low law enforcement, and minimal public participation in the planning and monitoring process. This study also identifies that the JIS area has not fully fulfilled the proportion of green space according to the stipulated standard. Therefore, concrete steps such as policy revision, strengthening of supervision mechanisms, and collaboration between the government, private sector, and civil society are needed in managing green spaces.